Hypertension Treatment Seeking Patterns and Healthcare Facility Accessibility - Ena Eppirta; Maidar Maidar; Asnawi Abdullah; Hermansyah Hermansyah; Fahmi Ichwansyah (GLOBAL HEALTH SCIENCE GROUP, 2025)
The World Health Organization (WHO) estimates that by 2025, approximately 29% of the global population will experience hypertension. The prevalence of hypertension in Aceh Province has increased by 21.5%. The Aceh Jaya District Health Office reported significant fluctuations in hypertension incidence at Krueng Sabee Community Health Center (Puskesmas), an area characterized by limited accessibility to health facilities due to varied topography, including highland, midland, and lowland regions. This study aimed to analyze the treatment-seeking patterns for hypertension and healthcare accessibility in the area, based on a population of 2,759 hypertensive patients registered at Krueng Sabee Puskesmas. Using a cross-sectional observational design, 335 respondents were selected through proportional random sampling. Data analysis was conducted using chi-square tests and spatial analysis. The results demonstrated significant associations between treatment-seeking patterns and factors such as age, hypertension status, education, occupation, income, and ease of transportation and information, while gender and distance showed no significant relationship. Among these factors, ease of transportation (OR = 12.591) was the most influential determinant of treatment-seeking behavior. Spatial analysis indicated that the distribution of health facilities was random (T = 1.212, p = 0.089). This study concludes that demographic and socioeconomic factors, along with transportation accessibility, significantly affect hypertension treatment-seeking patterns, whereas gender and distance do not. The random spatial distribution of health facilities suggests potential barriers to healthcare access in this region.